2023
DOI: 10.18805/ijar.b-5078
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Non Genetic Factors and Sire on Lactation Length in Frieswal Cattle

Abstract: Lactation length is a very important trait of dairy animals directly affecting the milk yield. Shorter or extended lactation lengths are not desirable as it affects the milk yield. Therefore the study of factors affecting lactation length is of most important. The present study was conducted on data of 9094 lactations collected from 3425 Frieswal lactating cattle (Holstein Friesian x Sahiwal cattle) born to 239 sires maintained at Military Farm, Pimpri, Pune, Maharashtra from the year 1983 to 2018 to quantify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Chopade et al. (2023) reported that parity, period of calving and season of calving had significant effect ( p < .001) on lactation MY and cows calved during rainy season and first parity had lowest MY. Uttam et al.…”
Section: Discussionmentioning
confidence: 99%
“…Chopade et al. (2023) reported that parity, period of calving and season of calving had significant effect ( p < .001) on lactation MY and cows calved during rainy season and first parity had lowest MY. Uttam et al.…”
Section: Discussionmentioning
confidence: 99%